2012
DOI: 10.1371/journal.pone.0051646
|View full text |Cite|
|
Sign up to set email alerts
|

Processing of Communication Calls in Guinea Pig Auditory Cortex

Abstract: Vocal communication is an important aspect of guinea pig behaviour and a large contributor to their acoustic environment. We postulated that some cortical areas have distinctive roles in processing conspecific calls. In order to test this hypothesis we presented exemplars from all ten of their main adult vocalizations to urethane anesthetised animals while recording from each of the eight areas of the auditory cortex. We demonstrate that the primary area (AI) and three adjacent auditory belt areas contain many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 69 publications
(123 reference statements)
1
78
0
Order By: Relevance
“…1, where VRB placements were more lateral and ventral than AI placements. These locations are similar to those previously determined in guinea pig (Wallace et al, 2000;Grimsley et al, 2012). The identification of locations was confirmed by differences in the first-spike latency (FSL) responses, which are significantly longer in VRB (Wallace et al, 2000).…”
Section: Placement Of Arrayssupporting
confidence: 86%
See 2 more Smart Citations
“…1, where VRB placements were more lateral and ventral than AI placements. These locations are similar to those previously determined in guinea pig (Wallace et al, 2000;Grimsley et al, 2012). The identification of locations was confirmed by differences in the first-spike latency (FSL) responses, which are significantly longer in VRB (Wallace et al, 2000).…”
Section: Placement Of Arrayssupporting
confidence: 86%
“…Anatomical analysis using multiple staining preparations in guinea pig found that the ventral (i.e., deeper) border of layer V is approximately 1190 lm below the ventral border of layer II for AI, though this value could vary between 580 and 1470 lm when comparing the distance between the closest and farthest borders of the cortical layers (Wallace and Palmer, 2008). Though it is unclear what depths correspond to specific layers in the VRB, cortical thickness has typically been found to be thinner in belt regions, though thickness could vary from 1.6 to 2.2 mm in comparison to the typical thickness of 2 mm in AI (Grimsley et al, 2012). The consistent range of values in our study with these expected anatomical depths supports that the CSD analysis is correctly identifying sites in layer V.…”
Section: Placement Of Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the first use of natural sounds in auditory neuroscience came from neuro-ethologists who investigated how conspecific vocalizations or communication signals were selectively processed in the auditory system of auditory specialists. These investigations in model systems led to the discovery of cricket-song selective neurons and their contribution to the females' phonotaxis behavior [77], of call selective neurons in frogs [78] and guinea pigs [79], of song selective neurons in songbirds [7,[80][81][82], of neurons selective to the echolocation signal in bats [5], and of brain regions selective for conspecific calls in primates [83]. Selectivity for conspecific communication calls can be reflected not only in the mean rate of single neurons but also (and sometimes only) in time-varying responses [84,85] or ensemble responses [86,87].…”
Section: Animal Vocalizationsmentioning
confidence: 99%
“…Harmonic complexes are important components of speech, music, and some animal communications (including guinea pig calls : Berryman 1976;Grimsley et al 2012). Harmonic complexes create a perception of pitch, a perceptual grouping feature that has received particular attention (reviewed in Plack et al 2005;Wang and Bendor 2010).…”
mentioning
confidence: 99%